Enhancing Secondhand Market Dynamics through Circular Economy Principles and Technological Advancements: A Bibliometric Analysis - Adilah Asma Amanina (Universitas Negeri Surabaya, 2025)
Given the increasing focus on sustainability and resource efficiency, the interest in the secondhand market as a vital segment of the circular economy has also risen tremendously. This paper offers a bibliometric analysis of the changing features of the secondhand market that focus on circular economy aspects and technological development that transform this market. In the scope of this review, we strive to establish how the integration of circular strategies such as reuse, recycling, and product life extension as well as advances in technology have improved market efficiency, accessibility experiences for consumers, and efficiency on nature. Important conclusions emphasize the role of digital platforms, blockchain, artificial intelligence, and the Internet of Things in improving the efficiency of product tracking, trust, and transaction transparency in the secondhand market. The knowledge acquired proposes ways in which some of the stakeholders can implement technological solutions to the circular economy and enhance the concept of circularity in the economy.